RESISTENSI PEREMPUAN TERHADAP TRADISI-TRADISI DI PESANTREN ANALISIS WACANA KRITIS TERHADAP NOVEL PEREMPUAN BERKALUNG SORBAN - Kamila Adnani; Wening Udasmoro; Ratna Noviani (Universitas Gadjah Mada, 2016)
Gender issue in a pesantren (Islamic Boarding House) is a part of larger gender issues in Indonesia,either in education or religion. The main indicator of gender issue in pesantren is a striking gap betweenmen and women. Themes related to this issue actually are not new for novels in Indonesia. Some novelsrelated to pesantren usually portray women as helplessness, subordinate, inferior, and marginalized.However, in Perempuan Berkalung Sorban (PBS) novel, the author tried to empower women throughhis writings. Women in PBS novel was portrayed as smart, brave, and critical towards pesantren’shegemony such as power relation between santri (students) and kiai (teachers), the understanding ofclassical books (Kitab Kuning), social relations between men and women in pesantren, and so forth